Modeling of RC columns strengthened with RC jackets. - Lampropoulos, A.P.
Constructing concrete jackets is a common technique when strengthening reinforced concrete (RC) columns, particularly is seismic regions. However, there are many uncertainties concerning the behavior of the composite specimen, particularly at the interface between the old and new concrete. In this paper, monotonic finite element (FE) analyses are performed to examine the behavior of strengthened columns under monotonic and cyclic loading. Through investigating two independent series of experimental results, it is demonstrated that monotonic FE analysis with appropriate assumptions can simulate both monotonic and cyclic loading conditions to a reasonable degree of accuracy. According to the results of this study, it is found that a simulation of the interface between the old and the new concrete is vital and cannot be ignored by simply considering a perfect bond at the interface. In the case of strengthened RC columns subjected to cyclic loading, strength degradation at the interface has to be included and can be effectively modeled by reducing the coefficients of friction and adhesion by using a proposed formula. Finally, the effect of jacket concrete shrinkage is simulated that leads to a reduced maximum load and stiffness of strengthened columns.
Keywords: Reinforced concrete; Columns; Concrete jacket; Modeling; Concrete interfaces; Shrinkage